2018
DOI: 10.3389/fpsyg.2018.02049
|View full text |Cite
|
Sign up to set email alerts
|

Low-Resolution Place and Response Learning Capacities in Down Syndrome

Abstract: Down syndrome (DS), the most common genetic cause of intellectual disability, results from the partial or complete triplication of chromosome 21. Individuals with DS are impaired at using a high-resolution, allocentric spatial representation to learn and remember discrete locations in a controlled environment. Here, we assessed the capacity of individuals with DS to perform low-resolution spatial learning, depending on two competing memory systems: (1) the place learning system, which depends on the hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 83 publications
6
16
0
Order By: Relevance
“…Our study thus revealed that in a real-world laboratory setting, individuals with DS exhibit cognitive mapping abilities that are similar to those of TD children within the same mental age range, whereas individuals with WS are comparatively impaired. These findings are consistent with previous findings suggesting a relative preservation of the ability to create and use low-resolution allocentric spatial representations in DS (Banta Bostelmann et al, 2018), and significant impairments in WS (Bostelmann et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our study thus revealed that in a real-world laboratory setting, individuals with DS exhibit cognitive mapping abilities that are similar to those of TD children within the same mental age range, whereas individuals with WS are comparatively impaired. These findings are consistent with previous findings suggesting a relative preservation of the ability to create and use low-resolution allocentric spatial representations in DS (Banta Bostelmann et al, 2018), and significant impairments in WS (Bostelmann et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Individuals with WS were severely impaired on this task: only 17% of the participants with WS tested (mean mental age 5.9 years) could solve the task, whereas 95% of TD children can solve the task from 3 years of age (Ribordy et al, 2013;Ribordy Lambert et al, 2015;Bostelmann et al, 2017). In contrast, 78% of the participants with DS (mean mental age 5.6 years) could solve the task (Bostelmann et al, 2018), thus exhibiting markedly better allocentric spatial capacities than participants with WS. These results provide the clearest evidence to date of the most basic cognitive mapping capacities of individuals with WS and DS, in a real-world laboratory setting enabling the integration of all sources of sensory information normally available when moving freely in the environment.…”
Section: Real-world Spatial Capacitiesmentioning
confidence: 95%
See 3 more Smart Citations